Measuring the Resistance of Tires for Passenger Vehicle against the Rolling and Sliding on Loading Area of the Flatbed Truck when Providing the Transport Services - Vrabel, Jan; Stopka, Ondrej; Rievaj, Vladimir; Sarkan, Branislav; Pruskova, Kristyna; Michalk, Philip (Communications - Scientific letters of the University of Zilina, 2016)
This paper deals with the size of the forces affecting the vehicle during the transportation on a flatbed truck, railway wagon or container. It is necessary to secure the vehicle against these forces properly in order to prevent vehicle´s replacement. The laboratory measurements were performed in order to find out the size of coefficient of friction between the tire and the vehicle´s loading area. During the measurements, vehicle had different gears in order to determine to what extent the size of mechanical resistances affects the fixing and securing the vehicle against its replacement on the loading area. However, this paper does not propose the solution for securing the passenger vehicle on the loading area of a truck, railway wagon or container.